Comparison of the value of PCNA and Ki-67 as markers of cell proliferation in ameloblastic tumor - Bologna-Molina, Ronell (Medicina Oral S.L., 2013)
Objectives: The aim of this study was to compare among PCNAand Ki-67 as the most reliable immunohistochemical marker for evaluating cell proliferation in ameloblastic tumors. Study Design: Observational, retrospective, and descriptive study of a large series of ameloblastic tumors, composed of 161 ameloblastomas and four ameloblastic carcinomas, to determine and compare PCNA and Ki-67 expression using immunohistochemistry techniques. Results: When analyzing Ki-67 positivity, the desmoplastic ameloblastoma demonstrated a significantly lower proliferation rate (1.9%) compared with the solid/multicystic and unicystic ameloblastomas and ameloblastic carcinomas (p<0.05), whereas the ameloblastic carcinomas displayed a significantly higher rate compared with all of the other ameloblastomas (48.7%) (p<0.05). When analyzing cell proliferation with PCNA, we found significant differences only between the ameloblastic carcinomas (93.3%) and the desmoplastic ameloblastomas (p<0.05). When differences between the immunopositivity for PCNA and Ki-67 were compared, the percentages were higher for PCNA in all types of ameloblastomas and ameloblastic carcinomas. In all cases, the percentages were greater than 80%, whereas the immunopositivity for Ki-67 was significantly lower; for example, the ameloblastic carcinoma expressed the highest positivity and only reached 48.7%, compared to 93.3% when we used PCNA. Conclusions: In the present study, when we used the proliferation cell marker Ki-67, the percentages of positivity were more specific and varied among the different types of ameloblastomas, suggesting that Ki-67 is a more specific marker for the proliferation of ameloblastic tumor cells. Key words:Ameloblastomas, ameloblastic carcinoma, PCNA, Ki-67, cell proliferation markers.